2000
DOI: 10.1046/j.1537-2995.2000.40050602.x
|View full text |Cite
|
Sign up to set email alerts
|

High rate of GB virus type C/HGV transmission from mother to infant: possible implications for the prevalence of infection in blood donors

Abstract: The frequency of mother-to-infant GBV-C/HGV transmission is elevated and could explain the high prevalence of GBV-C/HGV markers (viral RNA and E2 antibody) in adults at low risk for blood-borne or sexually transmitted viruses, such as blood donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…The rate of GBV-C viremia in individuals with HCV infection is 15% to 20%, and up to 40% among HIV-positive people who acquired HIV through sexual transmission [29••,30,36-38], supporting both parenteral and sexual modes of transmission of GBV-C. Several studies have found evidence that sexual transmission of GBV-C occurs [29••,42-47]. GBV-C may also be transmitted vertically, and 89% of infants of HIV-negative and HCV-negative women with GBV-C infection had GBV-C RNA detected between 3 and 9 months of life in one study [48].…”
Section: Gb Virus C Prevalence and Diseasementioning
confidence: 96%
“…The rate of GBV-C viremia in individuals with HCV infection is 15% to 20%, and up to 40% among HIV-positive people who acquired HIV through sexual transmission [29••,30,36-38], supporting both parenteral and sexual modes of transmission of GBV-C. Several studies have found evidence that sexual transmission of GBV-C occurs [29••,42-47]. GBV-C may also be transmitted vertically, and 89% of infants of HIV-negative and HCV-negative women with GBV-C infection had GBV-C RNA detected between 3 and 9 months of life in one study [48].…”
Section: Gb Virus C Prevalence and Diseasementioning
confidence: 96%
“…Parenteral exposure has been documented to be the main mode of transmission for GBV-C/HGV. Sexual and vertical transmissions appear to play an important role as well [Hadziyannis and Hess, 1998;Karayiannis and Thomas, 1998;Scallan et al, 1998;Bourlet et al, 1999;Lefrere et al, 1999Lefrere et al, , 2000Stark et al, 1999]. Whether other transmission routes might be operating for GBV-C/HGV remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of GBV-C infection in the general population is higher than that of other bloodborne viruses, such as human immunodeficiency virus (HIV) and hepatitis C virus in western industrialized countries and varies globally, as does GBV-C genotype. Among antenatal populations, the prevalence of GBV-C RNA varies from 1%-2% in East Asia [1,2] to 5%-7% in Europe, Australia, and Southeast Asia [3][4][5][6] and 10%-13% in Africa [7,8]. GBV-C infection is also more prevalent in HIV-infected persons and others with risk factors for bloodborne infections [9] and can be transmitted parenterally, sexually, and vertically [10].…”
mentioning
confidence: 99%
“…GBV-C infection is also more prevalent in HIV-infected persons and others with risk factors for bloodborne infections [9] and can be transmitted parenterally, sexually, and vertically [10]. Mother-to-child transmission (MTCT) of GBV-C has been hypothesized as one possible mechanism for the relatively high prevalence of GBV-C infection in the general population [4,11,12].…”
mentioning
confidence: 99%